2020
DOI: 10.1111/jam.14641
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma atroviride as a promising biocontrol agent in seed coating for reducing Fusarium damping‐off on maize

Abstract: Aims: The objective of this work was to identify a fungal strain showing potential biocontrol abilities against two Fusarium damping-off agents and to test it as a Biological Control Agent (BCA) in maize seed coating under field conditions. Methods and Results: A collection of native fungal strains associated with maize in Belgium was screened for antagonistic potential against Fusarium avenaceum and Fusarium culmorum. The strain with highest biocontrol potential was identified as an endophytic Trichoderma atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 36 publications
2
26
0
1
Order By: Relevance
“…In this study, we identified and investigated a coconut-scented T. atroviride strain LZ42 with a plant-growth-promoting effect and biocontrol activity. T. atroviride LZ42 formulated in talc exhibited a significant control effect on Fusarium wilt of tomatoes in greenhouses and promoted the accumulation of plant biomass and growth, which is consistent with the activity of another T. atroviride strain BC0584 [37].…”
Section: Discussionsupporting
confidence: 78%
“…In this study, we identified and investigated a coconut-scented T. atroviride strain LZ42 with a plant-growth-promoting effect and biocontrol activity. T. atroviride LZ42 formulated in talc exhibited a significant control effect on Fusarium wilt of tomatoes in greenhouses and promoted the accumulation of plant biomass and growth, which is consistent with the activity of another T. atroviride strain BC0584 [37].…”
Section: Discussionsupporting
confidence: 78%
“…By delivering materials such as micronutrients and crop protection agents such as pesticides, seed‐coating is an effective way to prevent seed‐ and soil‐borne diseases, and underground and even aboveground pests that attack seedlings. Because it significantly reduces the amount of pesticides required and increases the efficiency of disease control, coating has become a gold standard seed treatment in China 2–4 . Moreover, the coating formula improves plant cultivation by forming an artificial outer layer or surface film, coloring and pelleting 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Because it significantly reduces the amount of pesticides required and increases the efficiency of disease control, coating has become a gold standard seed treatment in China. [2][3][4] Moreover, the coating formula improves plant cultivation by forming an artificial outer layer or surface film, coloring and pelleting. 5 This enhances seed quality and germination, 6 early plant establishment, and abiotic stress alleviation 7 by altering the shape, weight and surface texture of the seed, improving seed-soil contact or manipulating imbibition (the absorption of water in soil).…”
Section: Introductionmentioning
confidence: 99%
“…Fusarium spp. is a ubiquitous soil-borne plant pathogenic fungus that can cause highly damaging infections characterized by severe decay of seeds, roots, stems, ears or kernels [1,2]. Fusarium verticillioides (Gibberella fujikuroi mating population A; teleomorph, Gibberella moniliformis Wineland) is the prevalent species of Fusarium in distinct landscapes [3,4], and the losses caused by this fungus can vary from 7% to 38% [5].…”
Section: Introductionmentioning
confidence: 99%